Erosion downstream of non-full flowing triangular culvert cutlets - Wong, Wan Ee. (2009)
In this project, observation and evaluation of erosion downstream of non-full flowing culvert outlets was conducted and presented. The main aim of this study is to identify the controlling parameters which affect local scouring of the sediment bed used, and to compare the present study with the previous works. The sediment consists of uniform, poorly graded coarse-grained sand. Experimental runs were conducted as a subcritical culvert flow outlet control, with a range of tailwater depth over brink depth ratio and flow rates represented as Densimetric Froude number, while keeping other variables constant. The duration of an experiment is approximately 48 hours, where the maximum extend of the scour has been reached.